An Enriching Encounter: STEM Education and the MI Approach - Martín Carrasquilla, Olga; Santaolalla Pascual, Elsa (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
The changes in the social, cultural, technological and economic framework of the last decades have generated new educational scenarios and led us to reflect on the demands of the 21st Century schools. The need arises to break down the barriers between disciplines through an approach that integrates them in the real world, thus promoting relevant and authentic learning experiences, like the combination of STEM Education and the IM approach together with the Competency-based approach. This teaching approach promotes active participation of citizens within society, a permanent access to knowledge, learning and a development of critical and reflective thinking as well as values.